Pengaruh Gerakan Oikumene Terhadap Kerukunan Beragama di Indonesia - Harjaya Situmeang; Meditatio Situmorang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The positive impact of the ecumenical movement can be seen in its influence on inter-religious harmony. By promoting dialogue, mutual understanding, and cooperation on humanitarian issues, the movement helps create space for interfaith solidarity. Several concrete initiatives, such as cooperation in disaster management, inclusive education, and peace campaigns, are examples of how the ecumenical spirit can be translated into concrete actions that strengthen relations between religious communities. In the context of Indonesian society, this movement also contributes to strengthening a national identity that respects differences but still upholds unity.